2017
DOI: 10.1155/2017/7265972
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Acute Malnutrition among Children Aged 6–59 Months in Public Health Facilities of Pastoralist Community, Afar Region, Northeast Ethiopia: A Case Control Study

Abstract: Background In low income countries, acute malnutrition continues to be the most important risk factor for illnesses and deaths. The aim of this study was to assess the determinants of acute malnutrition among children aged 6–59 months. Methods A facility based unmatched case control study was employed on 420 (140 cases and 280 controls) children aged 6–59 months with their caregivers between January 20 and February 20, 2014. Data was analyzed using SPSS version 20.0. A P value < 0.05 was considered statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 8 publications
4
22
0
Order By: Relevance
“…[14][15][16] It is also in line with findings of other studies in Ethiopia. [17][18][19][20][21] This might be due to the fact that mothers with formal education acquire knowledge which helps them to understand and obtain information on optimal child feeding and care practice through education, advice and media.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] It is also in line with findings of other studies in Ethiopia. [17][18][19][20][21] This might be due to the fact that mothers with formal education acquire knowledge which helps them to understand and obtain information on optimal child feeding and care practice through education, advice and media.…”
Section: Discussionmentioning
confidence: 99%
“…Exhaustive identification of such broad multi-sectoral factors will lead comprehensive intervention. Many studies in developing countries including Ethiopia showed that household characteristics like income, 9, 12 13, 14,15 less access to health service, 12,14 household head, 12,13,14 lack of toilet, 16,17 mothers education, 18,19,20 paternal education, 21 handwashing, 22,23,24 household food insecurity, 23,24 poor exclusive breast feeding, 25,22,26 and number of under-five children or family size 22,27,28 has explained the occurrence of acute malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…The odds of relapse were higher among children not given high dose Vitamin A supplementation in the 6 months preceding the survey. This may indicate low receipt of, or access to nutrition services such as distribution of Vitamin A capsule and has also been noted in Hawassa, and Afar region, Ethiopia (44,56). The protective role of Vitamin A in promoting and regulating activities in both the innate and adaptive immune system (57) enhancing immune function is the rationale for recommended supplementation every 6 months (58).…”
Section: Manuscript To Be Reviewedmentioning
confidence: 82%
“…This could be linked to malaria transmission by geographic area (43), or The difference could also be related to child food preparation practice (as one third of mothers from Lay-Gaying versus one tenth from Ebnat). A study in Afar region, Ethiopia found that children's food wasn't prepared separately from family food were more acutely malnourished (44) Children both in the recovered and in the comparison groups who were not given colostrum were found more acutely malnourished than those who were given colostrum. This is because colostrum has all the essential nutrients and immunoglobulin that are important in disease prevention.…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%